1967
DOI: 10.1246/bcsj.40.935
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Esters of Phosphoric Acid by the Reaction of Trivalent Phosphorus Compounds with Diethyl Azodicarboxylate in the Presence of Alcohols

Abstract: Trivalent phosphorus compounds, phosphine or trialkylphosphites, have been oxidized by means of diethyl azodicarboxylate and either benzyl or allyl alcohol to give the corresponding phosphine oxide or trialkyl phosphates. The reaction was then extended to the phosphorylation of alcohols. When allyl diethyl phosphite was treated with diethyl azodicarboxylate in the presence of an alcohol at room temperature, a corresponding alkyl diethyl phosphate and diethyl N-allyl hydrazodicarboxylate were obtained in good y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
109
0
6

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 281 publications
(115 citation statements)
references
References 2 publications
0
109
0
6
Order By: Relevance
“…For example, O-monobenzylated, Cmonobenzylated and C-dibenzylated products (5 : 45 : 50) were obtained by benzylation of ethyl acetate with benzyl bromide in dimethyl sulfoxide. 4) C-Alkylation of active methylene compounds with alcohols has recently been accomplished in a redox reaction system by Mitsunobu-type reactions, 5) and Tsunoda and coworkers 6) have also reported efficient methods for alkylation of active methylene compounds. However, with benzyl alcohol, it is reported that the concomitant double alkylation and/or an ether forming-reaction takes place.…”
mentioning
confidence: 99%
“…For example, O-monobenzylated, Cmonobenzylated and C-dibenzylated products (5 : 45 : 50) were obtained by benzylation of ethyl acetate with benzyl bromide in dimethyl sulfoxide. 4) C-Alkylation of active methylene compounds with alcohols has recently been accomplished in a redox reaction system by Mitsunobu-type reactions, 5) and Tsunoda and coworkers 6) have also reported efficient methods for alkylation of active methylene compounds. However, with benzyl alcohol, it is reported that the concomitant double alkylation and/or an ether forming-reaction takes place.…”
mentioning
confidence: 99%
“…It is well known that products of this type can be formed upon treatment of benzyl and allyl alcohols with DEAD and PPh 3 in the absence of a good nucleophile. 11 It is evident, however, that there is no reason why our AB 2 monomer 10i would show a lack of reactivity. Therefore, we think the extreme activation of benzyl alcohol 12 is likely to facilitate the formation of 16 to a notable extent.…”
Section: Methodsmentioning
confidence: 92%
“…[2][3][4] These reactions occur in a manner that is analogous to the Mitsunobu reaction, involving an intermediate alkoxyphosphonium salt. 5,6 The advantages of the Hendrickson reagent over the Mitsunobu reagent are that the recovered triphenylphosphine oxide may be recycled by treatment with trifluromethanesulfonic anhydride, the use of explosive azodicarboxylates is not required and competing side reactions are avoided. 7 Furthermore, a number of methods have recently been reported that can easily overcome, or avoid, the formation and removal of the double-stoichiometric amount of triphenylphosphine oxide, a common problem of phosphine-based dehydrating agents.…”
Section: Introductionmentioning
confidence: 99%